Feasibility study of applications of micro-bubbles for aquaculture - Kozima, Hiroyuki; Mukai, Yukinori; Ransangan, J.; Senoo, Shigeharu (INOC-UMS, 2006)
Micro-bubbles are ultra-fine gas bubbles in water, of which size is less than 50μm. As they are suspended in water, the bubbles shrink spontaneously to nanometer level and eventually disappear. The characteristic feature is the negatively charged surface and self-pressured effects, which may enable a variety of possibilities of applications for aquaculture. In 2004 a research group of National Institute of Advanced Industrial Science & Technology (AIST) in Japan succeeded in inactivation of norovirus in oyster aquaculture (Takahashi, 2004). Here we’ll discuss further possibilities of this new technology for aquaculture.